1990
DOI: 10.1200/jco.1990.8.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of continuous infusion fluorouracil versus fluorouracil plus cisplatin in patients with metastatic colorectal cancer.

Abstract: One hundred twenty-two chemotherapy-naive patients with histologically confirmed colorectal adenocarcinoma were entered into a randomized trial comparing infusional fluorouracil (FU) versus cisplatin (CDDP) and FU. In both groups, patients received continuous infusion FU 1,000 mg/m2/d for 5 consecutive days every 4 weeks. Patients randomized to CDDP/FU also received CDDP 20 mg/m2 intravenous (IV) bolus on days 1 to 5 of each cycle. Patients were comparable in terms of age, performance status, baseline laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(30 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…The combination chemotherapy of cisplatin and 5-FU has been proven to have synergic antitumor effect in many experimental and clinical studies (17,18). However, the optimal sequence for the administration of these drugs has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The combination chemotherapy of cisplatin and 5-FU has been proven to have synergic antitumor effect in many experimental and clinical studies (17,18). However, the optimal sequence for the administration of these drugs has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the rst study, with 122 patients, uorouracil:cisplatin provided a signicantly greater objective response rate (25% vs 3%; p ¾ 0.001) with increased toxicity, but no improvement in overall survival (10 vs 12 months) (106). In the second trial, 160 patients were entered (107).…”
Section: Fluorouracil In Combination With Cisplatinmentioning
confidence: 99%
“…The combination of fluorouracil with leucovorin is nowadays the more or less accepted standard treatment, but the optimum treatment schedule still has to be defined (Moertel, 1994). Cisplatin as a single agent at standard doses is inactive in colorectal cancer (DeSimone et al, 1986) but in combination with fluorouracil a modest activity has been reported (Posner et al, 1987; LoRuss et al, 1989;Kemeny et al, 1990). Etoposide as a single agent given intravenously is inactive in colorectal cancer (Perry et al, 1976;Douglass et al, 1979).…”
mentioning
confidence: 99%